Patient-Perceived Satisfaction and Knowledge Uptake in a Combined Cardio-Obstetrics Clinic - Karen L. Florio; Darcy White; Kensey Gosch; Neil Patel; Tara Daming; Emily M. Williams; Sarah Hostetter; Rebecca Gray; Lynne Nelson; Kathleen Swearingen; Christine Henricks; Anna Grodzinsky; et al. (Journal of Cardiovascular Development and Disease, 2022)
Heart disease is the leading cause of pregnancy-related mortality in the United States and has led to the development of combined cardio-obstetrics (COB) clinics as a model for prenatal care. In other areas of medicine, these types of collaborative care models have shown improvement in morbidity, mortality, and patient satisfaction. There is some data to suggest that a combined COB clinic improves maternal outcomes but there is no data to suggest patients prefer this type of care model. This study aims to evaluate patient satisfaction in a combined COB clinic and whether this type of model enhances perceived communication and knowledge uptake. A quality questionnaire was developed to assess patient perceptions regarding communication, satisfaction, and perceived knowledge. Patients who attended the clinic (n = 960) from 2014–2020 were contacted by email, with a response received from 119 (12.5%). Participants completed a questionnaire assessing satisfaction and perceived knowledge uptake with answers based on a Likert scale (7 representing very satisfied and 1 representing very unsatisfied). Safe and effective contraceptive use was evaluated by multiple choice options. Knowledge was also assessed by comparing contraceptive use before and after the clinic. Participants reported high levels of satisfaction with the clinic (6.2 ± 1.5), provider-to-patient communication (6.1 ± 1.6), and with the multidisciplinary appointment approach (6.3 ± 1.5). As well, participants reported an increase in knowledge about heart disease a result of collaborative counseling. In summary, a multidisciplinary approach to cardio-obstetrics not only improves outcomes but is a patient satisfier.